Copper–arsenic decoupling in an active geothermal system: A link between pyrite and fluid composition. (1st May 2017) - Tardani, Daniele; Reich, Martin; Deditius, Artur P.; Chryssoulis, Stephen; Sánchez-Alfaro, Pablo; Wrage, Jackie; Roberts, Malcolm P.
Abstract: Over the past few decades several studies have reported that pyrite hosts appreciable amounts of trace elements which commonly occur forming complex zoning patterns within a single mineral grain. These chemical zonations in pyrite have been recognized in a variety of hydrothermal ore deposit types (e.g., porphyry Cu–Mo–Au, epithermal Au deposits, iron oxide–copper–gold, Carlin-type and Archean lode Au deposits, among others), showing, in some cases, marked oscillatory alternation of metals and metalloids in pyrite growth zones (e.g., of Cu-rich, As–(Au, Ag)-depleted zones and As–(Au, Ag)-rich, Cu-depleted zones). This decoupled geochemical behavior of Cu and As has been interpreted as a result of chemical changes in ore-forming fluids, although direct evidence connecting fluctuations in hydrothermal fluid composition with metal partitioning into pyrite growth zones is still lacking. In this study, we report a comprehensive trace element database of pyrite from the Tolhuaca Geothermal System (TGS) in southern Chile, a young and active hydrothermal system where fewer pyrite growth rims and mineralization events are present and the reservoir fluid (i.e. ore-forming fluid) is accessible. We combined the high-spatial resolution and X-ray mapping capabilities of electron microprobe analysis (EMPA) with low detection limits and depth-profiling capacity of secondary-ion mass spectrometry (SIMS) in a suite of pyrite samples retrieved from a ∼1 km drill hole that crosses the argillic (20–450 m) and propylitic (650–1000 m) alteration zones of the geothermal system. We show that the concentrations of precious metals (e.g., Au, Ag), metalloids (e.g., As, Sb, Se, Te), and base and heavy metals (e.g., Cu, Co, Ni, Pb) in pyrite at the TGS are significant. Among the elements analyzed, As and Cu are the most abundant with concentrations that vary from sub-ppm levels to a few wt.% (i.e., up to ∼5 wt.% As, ∼1.5 wt.% Cu). Detailed wavelength-dispersive spectrometry (WDS) X-ray maps and SIMS depth vs. isotope concentration profiles reveal that pyrites from the TGS are characterized by chemical zoning where the studied elements occur in different mineralogical forms. Arsenic and Co occur as structurally bound elements in pyrite, Cu and Au in pyrite can occur as both solid solution and submicron-sized particles of chalcopyrite and native Au (or Au tellurides), respectively. Pyrites from the deeper propylitic zone do not show significant zonation and high Cu–(Co)–As concentrations correlate with each other. In contrast, well-developed zonations were detected in pyrite from the shallow argillic alteration zone, where Cu(Co)-rich, As-depleted cores alternate with Cu(Co)-depleted, As-rich rims. These microanalytical data were contrasted with chemical data of fluid inclusions in quartz and calcite veins (high Cu/As ratios) and borehole fluid (low Cu/As ratios) reported at the TGS, showing a clear correspondence between Cu and As concentrations in pyrite-forming fluids and chemical zonation in pyrite. These observations provide direct evidence supporting the selective partitioning of metals into pyrite as a result of changes in ore-forming fluid composition, most likely due to separation of a single-phase fluid into a low-density vapor and a denser brine, capable of fractionating Cu and As.